Coleta de dados em compreensão de leitura de textos médicos: Letramento em Saúde e Acessibilidade Textual e Terminológica - Finatto, Maria José Bocorny (2025)
The article synthesizes procedures and results from a reading comprehension test on medical texts conducted with Brazilian workers in outsourced cleaning, security, restaurant, reprography, and building maintenance services at two campuses of the Federal University of Rio Grande do Sul (UFRGS) in Porto Alegre - RS, Brazil. The theoretical-methodological framework is based on Terminology studies from a linguistic-textual perspective, incorporating principles of Readability and Textual and Terminological Accessibility (TTA). Among a population of approximately 400 workers, 46 individuals agreed to take the test. Pairs of short texts, one more complex and one simpler, were used on Parkinson's Disease (PD), Melanoma, and Bipolar Mood Disorder (BMD). The article presents the study’s basic procedures, the profile of the volunteers, the formatting of the texts used for testing, and a psychosocial questionnaire applied to respondents. Next, the results are summarized by respondent segments, including age groups, educational background, and familiarity with the topics. On average, the findings indicate better reading comprehension scores when respondents read the simplified texts, regardless of the topic. However, even the simplified texts on PD had lower comprehension scores. Nonetheless, for certain respondent groups, such as those aged between 40 and 44 years old, the simplification of BMD and Melanoma texts did not lead to better comprehension scores compared to the more complex versions. Finally, the results are discussed in terms of text types, considering the number of terminologies and vocabulary complexity, as well as reader profiles. The article concludes by addressing the perspectives and limitations of the study within the context of Education, Health Literacy, and TTA.